Growth of Makassar City as metropolitan have been increasing urban economic growth and social community change, however, it caused problems non-bus public passenger transport management policy not integrated with urban spatial planning policy as one unity. Research objectives are aimed to design model of sustainable transportation management for non-bus public passenger transport integrated with urban spatial planning, to evaluate existing route pattern performance and to identify and to manage - Umar Mansyur; Santun R.P. Sitorus; Marimin .; Lilik Budi Prasetyo; I.F. Poernomosidhi Poerwo (Forum Pasca Sarjana, 2009)
Growth of Makassar City as metropolitan have been increasing urban economic growth and social community change, however, it caused problems non-bus public passenger transport management policy not integrated with urban spatial planning policy as one unity. Research objectives are aimed to design model of sustainable transportation management for non-bus public passenger transport integrated with urban spatial planning, to evaluate existing route pattern performance and to identify and to manage potentially polluted corridor from emission gas. Research methods consist of three phases namely valuating of route performance with descriptive analysis, identifying gas emission and zoning management with level of services, hierarchy analytical process (AHP), and designing priority policy model with geographic information system (GIS) and exponential comparative method (MPE). The results are: (i) the road level of services performance with the bigger traffic composition are motorcycle and non-bus public passenger transport and densities of primary roads as compared to secondary roads with level of services of C, B, and A for variation between collector and artery roads; (ii) vehicle emission as standard of very small as compared to step over standard and gas ambient by CO are sedan/jeep, kijang, pick-up, bus, non-bus public passenger transport and mini bus, and mini truck on the artery road, (iii) the priority alternatives on zoning arrangement are first for environmental facility improvement, vehicle arrangement, location decision, and institutions arrangement; (iv) model of sustainable transportation management with GIS is spatial database and transportation maps of selected route and zoning arrangement whereas policy priorities are regarding management aspect improving level of service which consider road capacity, real speed, and volume ratio and regarding policy aspect ascertaining spatial plan as a dominant factor for zoning arrangement in relation to vehicle pollution. Key words: non-bus public passenger transport, sustainable, spatial, route, emission